2020
DOI: 10.2337/cd19-0101
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes Deserves More Attention: A Review

Abstract: Evidence increasingly demonstrates that prediabetes is a toxic state, as well as a risk factor for diabetes, and is associated with pathophysiological changes in several tissues and organs. Unfortunately, use of available evidence-based treatments for prediabetes is low. This review seeks to explain why prediabetes must be viewed and treated as a serious pathological entity in its own right. It offers an overview of the pathophysiology and complications of prediabetes and describes how this condition can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 76 publications
0
14
0
2
Order By: Relevance
“…Prediabetes represents an important public health concern, not only because it significantly increases the risk of progression to diabetes, but also because it has been associated with the development of diabetes-related complications [ 5 ]. Previous research suggests a bidirectional relationship between impaired glucose metabolism and depression, which means that each condition can increase the risk of developing the other [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prediabetes represents an important public health concern, not only because it significantly increases the risk of progression to diabetes, but also because it has been associated with the development of diabetes-related complications [ 5 ]. Previous research suggests a bidirectional relationship between impaired glucose metabolism and depression, which means that each condition can increase the risk of developing the other [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, our study found that being physically active was beneficial for reversion from prediabetes to normoglycemia. Moreover, the potential reason underlying the benefits of reversion from prediabetes to normoglycemia for the risk of death was primarily lifestyle modification …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the potential reason underlying the benefits of reversion from prediabetes to normoglycemia for the risk of death was primarily lifestyle modification. 29 …”
Section: Discussionmentioning
confidence: 99%
“…El interés por la prediabetes se ha incrementado notoriamente en las dos décadas de este siglo visto su trascendencia como estado metabólico y condición predisponente para la progresión futura a la diabetes tipo 2 (DM2) y enfermedad cardiovascular aterosclerótica (ECVA), además de que confiere una alta probabilidad de desarrollar muchas de las patologías normalmente asociadas a esa enfermedad, tales como retinopatía diabética, neuropatía periférica, enfermedad renal diabética y complicaciones macrovasculares 1 . La prediabetes representa una etapa intermedia de disglucemia a lo largo del continuo que va desde el estado normal a la Diabetes, se identifica mediante mediciones de laboratorio: valor de glucosa en ayuna, valor de glucosa 2 horas después de una carga de 75 grs de glucosa.…”
Section: Prediabetes and Its Complex Spectrum As A Challenge To Daily...unclassified